P379 Trends in Colectomy Rates and Biologic use over a, 30-year period: What has changed?. (21st January 2022) - Doherty, J; Stack, R; Fennessy, A; Cullen, G; Mulcahy, H; Sheridan, J; Kevans, D; Doherty, G
Abstract: Background: Novel medications including the introduction of biologic therapies in the last decade have expanded treatment options for patients with ulcerative colitis (UC). Large studies in the USA and Europe have shown colectomy rates in UC patients are reducing over the past two decades. Methods: We performed a single-centre retrospective study of our prospectively maintained IBD database. Our aim was to look at changes in colectomy rates in patients with UC over the past three decades and need for biologic therapy. Basic demographics, need for biologic therapy and colectomy rates were collected. Need for colectomy and biologic therapy within, 10 years of diagnosis was determined across three groups dependent on decade of diagnosis. Results: 2229 patients with confirmed UC were included in our study. Median age at diagnosis was, 37 years [range, 4.9 -92.6]., 1210 [54.28%] were male., 595 patients were diagnosed between, 1990–2000, 795 between, 2000–2010 and, 790 between, 2010–2020. A total of, 366 (16.4%) patients had a colectomy during follow-up and, 363 (16.3%) were treated with biologic therapies. We found rates of colectomy within, 10 years of diagnosis have significant dropped over the past three decades. From, 1990 -2000, 595 patients were diagnosed with UC and, 131 [22%] patients had colectomies, in, 2000-2010, 794 patients were diagnosed with UC and, 135 [17%] had a colectomy and between, 2010-2020, 784 patients were diagnosed with UC and, 55 [7%] had a colectomy [p = <, 0.001]. We found a significant increase in use of biologic therapy within the first, 10-years of diagnosis over the last three decades increasing from, 0.2% to, 5.3% to, 22.7% over the past decade [p = <, 0.001]. Conclusion: Management of UC has changed over the past three decades including the introduction of multiple biologic therapies and the use of therapeutic drug monitoring has allowed a more personalised approach to management of UC. We can see from this study changes in the management of UC over the past decade have resulted in significant reduction in need for colectomy and an increase in the use of biologics.